FEASIBILITY STUDY ANALYSIS OF BUSINESS MINGGON TOURISM MARKET, JATINAN, BATANG DISTRICT - Wardah Mahirdini (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2023)
Culinary tourism is a form of tourism that focuses on food as an attraction for exploration and tourism purposes. "Minggon Jatinan" is one of the culinary tours in Batang Regency. The purpose of this study is to suggest a framework to be used as a business development strategy for culinary tourism using qualitative research methods (surveys and observations). SWOT analysis is used to identify strengths, weaknesses, opportunities and threats. The findings of this study are related to the "Minggon Jatinan" culinary tourism development strategy, including the importance of implementing the strategy itself, collaboration between stakeholders, promotion of culinary profiles and optimizing the potential of existing forest natural resources to maintain the uniqueness of "Minggon Jatinan" culinary tourism in Batang Regency. has a tradition called Minggon Jatinan which is one of the media for introducing traditional culture in Indonesia. Minggon Jatinan was carried out in the Rajawali City Forest which is next to the northern coast road. Minggon Jatinan has a great attraction for tourists from within and outside Batang. The strategy in the Minggon Jatinan Tradition can benefit many parties. Apart from increasing development through several community groups, this tradition also strengthens relations between communities in Batang Regency.